'Naturally occurring' anti-D in Rh(D) negative volunteers for immunization - Lee, D; Remnant, M; Stratton, F (Clinical and laboratory haematology, 1984)
'Naturally occurring' anti-D has been studied in four Rh(D) negative males. The presence of this anti-D does not preclude successful deliberate immunization of Rh(D) negative volunteers; 'naturally occurring' anti-D does not provide a marker of non-responders to Rh immunization. 'Naturally occurring' anti-D is not necessarily the result of materno-fetal transfusion at birth.